The “casas-hogar” project for the children of Morelia (1943-1948) (Tzintzun, Revista de Estudios Históricos, 2016)
he present paper seeks to analyse a project of creating and running a systemof lodgings which were created to accommodate the so-called “children ofMorelia”. he ordeal of the 464 Spanish children who arrived in Mexico in1937 was marked by a strong polemic and political ights from the moment oftheir arrival. As they were the object of propaganda between opposing politicalgroups, their integration in Mexico was made diicult and it also afectednegatively the development of the centre which hosted them. Around 1943,the situation in the Spanish-Mexican school of Morelia was no longer sustainableand the authorities decided to close it down. As most youngsters quitschool or were just about to inish their primary school studies, some helphad to be ofered to them so that they could continue their studies or look fora job without being let alone or cut of from their peers. It is in this contextthat the “casas-hogar” (‘houses-home’) Federación de Organismos de Ayudaa los Republicanos Españoles (FOARE) Project started, which worked relativelysuccessfully for ive years. he article analyses the economic and institutionaldevelopment of these lodgings, as well as the life conditions of its inhabitants.
Keywords: Spanish republican exile; children of Morelia; CAFARE; CTFARE; FOARE; casas-hogar